Volatility estimates of the short term interest rate with an application to German data - Henning Dankenbring (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
This paper proposes a procedure for testing alternative specifications of the short term interest rate's dynamics which takes into account that according to some restrictions the interest rate is nonstationary, i.e. the traditional test statistic has a non-standard distribution. Moreover, we do not take the specification of the mean equation as given by the theory but rather base the decision of the lag structure on a robust Lagrange Multiplier test. In contrast to U.S. data we find that the volatility depends on either the interest rate level or information shocks but not on both. Finally, we propose to describe the short term interest rate's dynamics by means of an AR(1) model with stochastic volatility.
urn:nbn:de:kobv:11-10060674
Keywords: C2; E4; G1; 330; Term Structure Models; Stochastic Volatility; ARCH